Assessment of the impact of chemicalization processes on the collection major crops. Issue 3 (December 2021) - Ivanova, T; Arkhipova, V; Antonovskaya, E; Sokolova, G; Brenchagova, S; Ivanova, A
Abstract: The Russian Federation has a significant raw material, scientific, technical, production and consumer potential necessary for the development of the mineral fertilizer industry. The amount of fertilizers used to increase soil fertility is one of the factors that determine the solution to the problem of the country's economic and food security. The purpose of this article is to develop a methodology for assessing the impact of the chemicalization process on the collection of major agricultural crops in the Russian Federation. To write it, methods such as: correlation and regression analysis, index analysis, calculation of the integral indicator, forecasting are used. The novelty of the conducted research lies in the following sequence of actions. Based on the statistics, we performed an index analysis of seven parameters; calculated an integral indicator that allows us to consider factors with a heterogeneous metric; assessed the impact of the chemicalization process on the collection of major crops. Further (using the Excel program), we developed a forecast for the development of chemicalization processes in agriculture until 2022 according to three scenarios: optimistic, probabilistic and pessimistic. Forecast quality indicators indicate that the optimistic and probabilistic scenarios are more likely to be realized. Thus, based on the obtained forecast data, it can be stated that it is necessary to adjust certain indicators that actively influence the rate of harvesting of the main agricultural crops, which is a mathematical justification for making managerial decisions in the development of strategies and programs for the chemicalization of agriculture in the Russian Federation, in order to develop it further.